COVID-19 supply disruptions and process innovations - Vos, Rob (2021)
Rob Vos GLOBAL FOOD POLICY REPORT GLOBAL LAUNCH EVENT - 2021 Global Food Policy Report: Transforming Food Systems After COVID-19 APR 13, 2021 - 09:30 AM TO 11:00 AM EDT